Numerical Simulation of Plasma Plume With Gas-Surface Interaction and Chemical Reaction Coupling Effect Based on DSMC-PIC Parallel Algorithm - Yang, Fuxiang; Li, Jie; Du, Wendi (IEEE transactions on plasma science, 2023)
The spatio-temporal evolution of plasma plumes is accompanied by a series of complex chemical reactions and gas-surface interactions that crucially affect the working characteristics and performance of plasma devices. The direct simulation Monte Carlo (DSMC) and particle-in-cell (PIC) hybrid parallel algorithm is often used to numerically simulate such phenomena. This article discusses the gas-surface interaction models of neutral molecules as elucidated by the parallel DSMC-PIC program. These models include the Maxwell model, the Cercignani-Lampis-Lord model, the complete diffuse reflection (CDR) gas-surface reflection model, and coupling with H combined reactions at the wall. Meanwhile, we consider the ion gas-surface interaction models, which include the CDR model and coupling of the four wall chemical reactions of ions. In addition, the dissociation reactions of H _{2} and recombination reactions of H are considered in the flow field. For various combinations of models, the simulations reveal the structural characteristics, number density, and coupling effects of gas-surface reflections, gas-surface chemical reactions, chemical reactions in the flow field and electric field, and spatio-temporal evolution of H _{2} , H, X , H _{2}^{+} , and H ^{+} , which are shown by the structural characteristics of the number-density contours for different model combinations and analyzed in detail. The gas-surface interaction critically influences the number-density distribution near the wall and in the main flow. It also strongly affects the number-density distribution of light neutral molecules but not heavy neutral molecules and ions and produces the wall stacking effect. Apart from the stacking area, it has an indirect influence on the number-density distribution. The chemical reactions of ions on the wall affect the number-density distribution of all particles in the flow field and decisively affect the ions near the wall. Acceleration by the electric field intensifies the ion diffusion. The effect of coupling of gas-surface interaction and acceleration by the electric field is obvious. Via the number density and temperature, the chemical reactions in the flow field strongly affect the distribution of neutral molecules at the inlet; further, from the inlet, this effect weakens. Neutral particles and ions interact mainly through collisions.